PENGARUH PENERAPAN STRATEGI DOMINO GAME TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 26 PADANG - Ramadhani, Ramadhani; Zulfaneti, Zulfaneti; Pratiwi, Merina (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ The research was conducted based on the fact which indicated the low studentsâ comprehension about mathematical concept and the low studentsâ motivation to think during the learning process in the VIII grade students of SMPN 26 Padang. The purpose of the research was to know whether the VIII grade studentsâ comprehension in mathematical concept treated by Domino Game strategy was better than the studentsâ comprehension treated by conventional strategy.Â This was an experimental research which used random sampling. The instrument used was the post test. The hypothesis testing showed that t-obtained (2.332) was bigger than t-table (1.67). Thus, it can be concluded that the studentsâ treated by Domino Game strategy had better comprehension of mathematical concept than those who treated by the conventional learning.